SISTEM INFORMASI ELEKTRONIK PELAYANAN TERPADU SATU PINTU (EPTSP) PADA KEJAKSAAN NEGERI MUARO JAMBI : System;Information;Electronic;Technology. - Purnama, Fery; Adhiatma, Novri; Ikhsan, Muhammad (FORTECH (Journal of Information Technology), 2022)
Technology is a tool that is used today to facilitate human work both in everyday life and in organizations. Currently, the services carried out by the Kejaksaan Muaro Jambi in serving the community still serve conventionally and require a long time, so that the services at the Kejaksaan Muaro Jambi are still divided into several parts and lack transparency. Based on this problem, the researcher will build a service system that can be accessed at one door as stated in the One Stop Service Implementation (PPTSP) in accordance with the Regulation of the Minister of Home Affairs Number 24 of 2006 and the Circular Letter of the Minister of Home Affairs Number 188.32/498/V/Bangda concerning the Implementation Guidelines for the Minister of Home Affairs Number 24 of 2006, has goals and objectives to realize public services that are fast, cheap, easy, transparent, certain and affordable, as well as being able to improve the rights of the community in public services. Researchers have a goal to build an electronic information system for one-stop integrated services to facilitate and improve services to the public by the Kejaksaan Muaro Jambi. In building the system, the researcher will use the method in stages starting from data collection, needs analysis, system design, system design, and system implementation and testing until the system can run well. The system built can be accessed with only one portal by having many services in it without having to open service portals one by one and also the system built can be accessed from anywhere and anytime to make it easier for the public to report and get information from the Kejaksaan Muaro Jambi. The EPTSP of the Kejaksaan Muaro Jambi is very useful in improving service and employee performance as well as making it easier for the public to get information from the Kejaksaan Muaro Jambi quickly and accurately.